Connecting people with city cultural heritage through proximity-based digital storytelling. (September 2018) - Nosrati, Fariba; Crippa, Claudia; Detlor, Brian
This paper describes a research investigation on a project led by two libraries, Hamilton Public Library and McMaster University Library, in Hamilton, Canada, concerning the use of proximity-based technologies to share digital stories about a city's culture. Proximity-based technology systems, such as iBeacons, allow users to receive information automatically when they are close to a physical spot. The project involved the setup of iBeacons that disseminated digital stories pertaining to Gore Park – a prominent historical park in the heart of downtown Hamilton. To test the viability of using iBeacon technologies to raise interest in a city and promote appreciation for a city's cultural heritage, a pilot study was conducted. The study included one-on-one interviews and a short survey with 50 participants from the general public immediately after these participants used an iBeacon app to experience digital stories about Gore Park. Findings suggest iBeacons are viable tools to share city cultural heritage stories that yield improved perceptions of a city and greater appreciation for a city's culture and history. Participants were appreciative of the digital stories and the iBeacon app. All participants mentioned that they learned something new about the city and that the app was very informative. Findings indicate that individual differences are important and can affect not only the acceptance and use of an iBeacon digital storytelling app, but also the extent to which the app can promote interest in a city and appreciation for a city's cultural heritage.